Pengembangan Instrumen Tes Kemampuan Berpikir Analisis Pada Materi Akhlak Terpuji Dalam Pergaulan Remaja - Diki, Diki Mulyana; Farida, Ida; Hardiansyah, Darius (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
The quality of the cognitive learning outcomes instrument is one of the prerequisites that must be considered by the teacher before evaluating student learning outcomes. However, the reality in the field is that some of the learning outcomes instruments used do not seem to have applied the appropriate rules. This study aims to develop a test instrument for analytical thinking skills in Akidah Akhlak subjects, commendable morals in adolescent association. This research was carried out at MTs Miftahul Huda in Bandung, involving 31 students. The method used in this study is Research and Development (R&D) with the ADDIE model. The instruments developed are oriented to analytical thinking skills. Based on the test results obtained (1) All test items (12 items) are valid both content and construct, while based on the empirical validity test 3 items are declared invalid; (2) the reliability coefficient is 0.786 at a significance of 0.05 has a high level of reliability; (3) the difficulty index of the items in the easy category with a percentage of 60% and the medium category 40%; (4) the discrepancy index of 13 items is categorized as good with the calculation results showing a positive value; and (5) the effectiveness of the distractor is stated that the 13 item questions or as much as 75% of the distractors function well, while 2 items or 25% must be corrected. Thus, the developed instrument is suitable to be used as an analytical thinking ability test instrument.